Analysis of risk factors for postoperative dysphagia after C1-2 fusion - Sun, Dong; Mou, Jianhui; Wang, Zhaolin; Liu, Peng (Frontiers in Surgery, 2022)
Study Design: Retrospective study Objective: This study aimed to analyze the risk factors for dysphagia after C1-2 fusion in patients with craniocervical junction diseases. Summary of the background Data: Dysphagia is a common postoperative complication of posterior craniocervical junction surgery. The incidence is 9.5% to 26.3%. However, the etiopathogenisis of postoperative dysphagia remains controversial. Methods: This retrospective study included patients who underwent C1-2 fusion from January 2016 to January 2020. The patients were divided into dysphagia group and control group in accordance with the BAZE dysphagia scoring system. The patients’ age, gender, BMI(body mass index), cause of disease, and changes in the C01cobb, C02cobb, C12cobb, C27cobb, dC02cobb, dC01cobb, dC12cobb, d C27cobb angles before and after operation, were recorded. The parameters and changes were compared to analyze the risk factors for dysphagia after C1-2 fusion. Results: 65 cases (15, with dysphagia; 50, without dysphagia) were included. The incidence of postoperative dysphagia was 23%. The differences in age, gender ratio, and BMI between the two groups were not significant (P>0.05). The differences among postoperative C12 (29.8°±11.24° vs. 20.46°±13.39°), postoperative C27cobb (10.56° ± 8.53° vs. 20.21° ± 13.21°), and dC12cobb (9.49° ± 5.16° vs. 1.07° ± 12.44°) between the two groups were significant (P<0.05). Multiple logistic regression analyses revealed that dC12cobb>5° was a significant independent risk factor for postoperative dysphagia, And preoperative C27cobb was a preventive factor of postoperative dysphagia. Conclusions: Dysphagia after the C1-2 fusion was common. dC02cobb and dC12cobb were the significant independent risk factors for postoperative dysphagia. Preoperative c27cobb was a preventive factor of dysphagia.